Faktor Risiko Terjadinya Syok pada lnfeksi Dengue Anak Di RSUD Panembahan Senopati Bantul - Dwi Kartika Sari; MTS Darmawan (Faculty of Medicine, Universitas Islam Indonesia, 2010)
Dengue is a important viral disease for public health issues. Compared to the 1950s where only nine countries have reported the case, then now is the geographic distribution has included more than 112 countries in the world. World Health Organization (WHO) estimates that about 2. 5 billion people on earth have a risk of dengue infection. Most of them have symptoms asymptomatic. A large number of cases mentioning that in 2005 there were 50,196 cases of dengue in Indonesia. The district of Bantu/ did not escape from the threat of dengue infection. The main cause of mortality of dengue virus infection is dengue hemorrhagic fever and dengue shock syndrome. The incident of shock is inflt,Jenced by several factors that are difficult issue in the treatment of dengue hemorrhagic fever severity. The purpose of this study is to identify risk factors the incidence of shock dengue hemorrhagic fever patients in children at RSUD Panembahan Senopati, Bantu/. This study use cross-sectional method. The samples were collected from children age 1-15 years who were treated at RSUD Panembahan Senopati, Bantu/ period January to December 2010 with DHF and DSS. Clinical symptoms and laboratory result are taken from medical record. Univariate analysis using the frequency distribution table and bivariate analysis · using the chi-square test. Sixty subjects include in this study, thirty subjects DHF and thirty subjects DSS. Using bivariate analysis we found that headache (OR 0,082; Cl 05%: 0,016-0,406), hepatomegaly (OR 6,000; Cl95%: 1,482-24,299) and WBC <4.000/mmk (OR 0,335; C/.95%: 0, 117-0,958) arf:J shock risk fActors in dengue hemorrhagic fever. Conclutions from this study are headache, hepatomegaly and WBC <4.000/mmk are shock risk factors in dengue hemorrhagic fever.